Prediction of breast cancer risk based on profiling with common genetic variants - Mavaddat, Nasim; Chang-Claude, Jenny; Rudolph, Anja; Seibold, Petra Beate; Burwinkel, Barbara; Marmé, Frederik; Schneeweiss, Andreas; Sohn, Christof; Sutter, Christian; Yang, Rongxi; Brauch, Hiltrud; Hamann, Ute; et al. (Journal of the National Cancer Institute, 2015)
AbstractBackground:. Data for multiple common susceptibility alleles for breast cancer may be combined to identify women at different levels of breast cancer r